Francisco Pizarro - Donaldson-Forbes, Jeff (New York The Rosen Publishing Group, Inc., 2002)
Provides information about explorer, Francisco Pizarro.
Keywords: Pizarro, Francisco, ca. 1475-1541.; Peru - History - Conquest, 1522-1548.; South America - Discovery and exploration - Spanish; Explorers - Peru - Biography; Explorers - Spain - Biography